2019
DOI: 10.1177/1945892419825612
|View full text |Cite
|
Sign up to set email alerts
|

Head and Bottle Angles Achieved by Patients During High-Volume Sinonasal Irrigations

Abstract: Background Certain head positions can optimize topical irrigation distribution to specific sinuses. No studies have assessed whether patients attain these positions when irrigating. Objective The purpose of this study was to assess head and bottle angles achieved when patients irrigate based on instructions from an irrigation device or from a Rhinologist. Methods Study approval was obtained from Henry Ford Health System’s Institutional Review Board (10604). Forty-two patients with various rhinologic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Head Positioning . Head position improves delivery in the previously operated patient, especially for low volume devices 1260,1261 . Very limited sinus delivery occurs in the unoperated patient regardless of head position.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Head Positioning . Head position improves delivery in the previously operated patient, especially for low volume devices 1260,1261 . Very limited sinus delivery occurs in the unoperated patient regardless of head position.…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…The findings of the cumulative studies show that surgery followed by high volume delivery devices are critical for effective delivery of topical therapies within the paranasal sinuses. 1259 t 1077,1085 Head position appears to affect distribution 1260,1261 but neither position nor volume seems to overcome the influence of surgical state 1262 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…The 3D-printed model may also educate patients on the importance of the precision of head angles. Griggs et al (21) showed that patients in a rhinology clinic irrigated on average about 20° up-rotated on lateral view, and vertex rotated 10° away from the side of irrigation on frontal view. As was shown in the current study, head positions are not all created equal, and perhaps with a 3D printed model, patients would be more likely to irrigate in a more precise manner since they know an error will not result in maximal sinus delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Although head tilt positions with large angle (e.g., nose-to-floor or nose-to-ceiling head position) was optimal to irrigate during the irrigation, it may be difficult for patients of different age to adopt and maintain the position [ 31 , 32 ]. Therefore, relatively low water volume, high irrigation efficiency, and a comfortable head position to follow were desirable strategies for choosing the nasal irrigation technique.…”
Section: Discussionmentioning
confidence: 99%